Maturity, pulp removal and storage effects on the germination of Livistona rotundifolia seeds - Viana, F. A.P. [UNESP]; Môro, F. V. [UNESP]; Batista, G. S. [UNESP]; De, G. [UNESP]; Mazzini, R. B. [UNESP]; Pivetta, K. F.L. [UNESP] (Int Soc Horticultural Science, 2013)
The Livistona rotundifolia species is native to Oceania, and has a high potential for landscaping use and as a pot plant. This work aimed to study the effects of the maturation stage, pulp removal and storage on the germination of L. rotundifolia seeds. The experimental design was entirely randomized in a factorial arrangement 5×2×2 (five storage periods: 15, 30, 45, 60 and 75 days; two maturation stages: green and ripe; and the presence or absence of the pulp - exocarp and mesocarp) with four replications of 25 seeds each. After sorting out the fruits by the maturity stage and removing the pulp out of half of the fruits from each plot, the seeds were placed in closed bottles, which were sealed and stored in a cold chamber at 10°C. The seeds were removed from the cold chamber and left to germinate in plastic boxes (gerbox type) with sphagnum. The boxes were kept at 25-35°C and photoperiod of 12 hours. The germination rate was determined when seed germination was steady. The highest germination rate was found when green fruits had their pulp removed. The germination rate gradually decreased with the increase of the storage period regardless the maturation stage and the presence or absence of the pulp.
Keywords: Arecaceae; Germination rate; Ornamental; Palm; Seed propagation